A Survey of Pharmacy Education in Thailand - Chanakit, Teeraporn (Am J Pharm Educ, 2014)
Objective. To explore the current status of pharmacy education in Thailand. Methods. The International Pharmaceutical Federation of the World Health Organization’s (FIP-WHO) Global Survey of Pharmacy Schools was used for this study. The survey instrument was distributed to the deans of the 19 faculties (colleges) of pharmacy in Thailand. Results. More than half the colleges have been in existence less than 20 years, and the government owns 80% of them. There were 2 paths of admission to study pharmacy: direct admission and central admission system. The doctor of pharmacy (PharmD) programs can be divided into 4 types. Approximately 60% of all teaching staff holds a doctoral degree. Regarding the work balance among teaching staff, around 60% focus on teaching activities, 20% focus on research, and less than 20% focus on patient care services concurrent with real practice teaching. The proportion of student time dedicated to theory, practice, and research in PharmD programs is 51.5%, 46.7%, and 1.8%, respectively. Sites owned by the colleges or by others were used for student training. Colleges followed the Office of the National Education Standards’ Internal Quality Assurance (IQA) and External Quality Assurance (EQA), and the Pharmacy Council’s Quality Assessment (ONESQA) . Conclusion. This study provides a picture of the current status of curriculum, teaching staff, and students in pharmacy education in Thailand. The curriculum was adapted from the US PharmD program with the aim of meeting the country’s needs and includes industrial pharmacy and public health tracks as well as clinical tracks. However, this transition in pharmacy education in Thailand needs to be monitored and evaluated.